Studi Implementasi Pembelajaran Berdiferensiasi di Pendidikan Dasar - Annisa Nidaur Rohmah (IBTIDA', 2023)
This study aims to describe the concept implementation of differentiated learning in Elementary school. This research uses the library research method or library research. Basically, this literature study uses journals or scientific articles, books, and other references besides the results of research related to both of them are used as supporting data which is then analyzed in such a way as to provide more meaningful information. As for the results of this study, it is known that in differentiated learning the four aspects that are in the control or control of the teacher are Content, Process, Product, and Classroom Learning Environment.